The leadership engine how winning companies build leaders at every level - Tichy, Noel M. (London Harper, 2007)
In this Wall Street Journal and BusinessWeek bestseller, Michigan Business School guru and worldwide consultant Noel Tichy brings his special brand of organisational transformation to a practical level that guarantees a leader at every level of an organisation.
Includes bibliographical references and index.
Keywords: Leadership